Kontribusi Motivasi Belajar dan Literasi Digital terhadap Hasil Belajar pada Mata Pelajaran Informatika Kelas X di SMK Negeri 1 Padang - Oktafia, Septina; Huda, Yasdinul (Lembaga Yasin AlSys, 2025)
This study employed an associative method with a correlational approach to examine the contribution of learning motivation and digital literacy to the learning outcomes of Grade X students in the Informatics subject at SMK Negeri 1 Padang. The research population consisted of 97 students, with a sample of 50 students selected using a simple random sampling technique and proportional allocation based on the Taro Yamane formula. The independent variables were learning motivation and digital literacy, while the dependent variable was learning outcomes. Data were collected through a Likert scale questionnaire to measure learning motivation and digital literacy, as well as documentation of Midterm Exam scores as an indicator of learning outcomes. Instrument validity and reliability were tested using the product moment correlation and Cronbach’s Alpha with the assistance of SPSS. Data analysis was conducted using descriptive statistics and multiple linear regression, accompanied by classical assumption tests (homogeneity, normality, linearity, multicollinearity, and heteroscedasticity). The results show that learning motivation contributed significantly by 75.6%, digital literacy contributed 17.5%, and together they contributed 93.1% to students’ learning outcomes. These findings affirm that learning motivation and digital literacy play crucial and complementary roles in improving Informatics learning outcomes at SMK Negeri 1 Padang.